What do we think are the most important journals in regional science? - Gunther Maier (European Regional Science Association (ERSA), 2005)
This paper reports the results of a survey about important journals in regional science. A web-based survey among regional scientists produces results about their opinion about the quality and reputation of regional science journals. The results are analyzed for stability over various characteristics of respondents like age, affiliation, nationality, main area of specialication, etc. The results are also compared to those derived from an analysis of publication records, citations and impact factors.
Keywords: 330